Students' evaluation on the effectiveness of the diploma of early childhood education programme in a private higher learning institution / Norazura Abd Hamid - Abd Hamid, Norazura (2012)
In the course of teaching early childhood education field, teachers for early years must be trained and qualified academically at least at Diploma level in early childhood education. The demand for academic qualification in diploma level for early childhood education (DECE) seems to be increasing from time to time and it was introduced in 2006 with the aim of training early childhood teachers to meet the increasing needs of teachers in this field. The study aims to examine the perception of students in Cohort 8,9,10 and 11 from one private institution on the effectiveness of the diploma in early childhood education programme. The methodology used was a mixed method i.e. using both quantitative and qualitative approaches. The study focuses on the strength and weakness of the programme offered, students' views with regard to teachers' knowledge in the subject matter, teachers' pedagogical knowledge and teachers 'personality. Some of the findings that deserve attention and consideration are: the students have comparatively high ratings of the lecturers' knowledge in the subject taught in terms of their preparation, presentation and adequate assignment and covering all topics in the syllabus. On the pedagogical knowledge, high ratings are given to lecturers' competency in handling teaching and learning process, lecturers use proper teaching aid when teaching in class, lecturers completed all the topics in the syllabus in time given and lecturers are well prepared for the lesson. On the personality traits, high ratings are given to lecturers' strong interpersonal skills in handling teaching and learning process, punctuality of lecturers in attending classes. Fair and low rating is given to lecturers' enthusiasm in caring, helpful and approachable to students and lecturer's capability to gives students motivation and creates students' interest for learning. The implication emphasizes on teachers' responsibility on creating conditions for effective learning environment. On the relevancy of subject offered; students give high ratings on subjects offered and are relevant to their career and personal development. All these factors need to be considered by college management for better improvement in teaching effectiveness and quality of programme offered.